Displays of cultural hegemony and counter-hegemony in the late Bronze and Iron age Levant - Thompson, Shane M., author.
1 online resource
Keywords: "This volume examines the power relationships between the rulers of the Late Bronze and Iron Age and their subjects in the Levant through the lens of "cultural hegemony". It explores the impact of these foreign powers on all social classes and reconstructs the public presence of cultural control. The book serves to determine the impact of foreign control on the daily lives of those living in the ancient Levant, and offers a means by which to attempt to discuss non-elites in the ancient Near East. It examines expressions of foreign ideology within public performance such as religious expressions and in public places, observable by all social classes, which assert control or dominance over local identity markers. In utilizing textual, epigraphic, and archaeological records, it paints a more complete picture of Levantine society during this time while also drawing upon evidence from neighbouring Anatolia, Egypt, and Mesopotamia. This is a fascinating resource for students and scholars of the ancient Near East, particularly the Levant but also Anatolia, Egypt, and Mesopotamia in the Late Bronze and Iron Age periods. It is also useful for scholars working on power and imperialism across history"--